2021
DOI: 10.1038/s41598-021-91411-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sliding liquefaction on homogeneous loess landslides in western China

Abstract: Sliding liquefaction is considered to be the cause of high-speed and long-distance sliding of some homogeneous loess landslides in western China. However, there is still a lack of necessary experimental research and analysis on the effects of sliding liquefaction on these landslides. In this work, the effects of sliding liquefaction on irrigation-induced, high-speed and long-distance loess landslides on the South Jingyang Tableland area in China are studied by performing large-scale ring shear tests and using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Also, Hong et al, (2021) based on their studies suggested that liquefaction could be the cause of some rapid landslides and great displacement in uniform loess slopes. Based on the eld survey and examination of a landslide that occurred in a village in the Xiangning Province of China in 2019, Shi et al, (2020) showed that the penetration of surface water into weak layers in the depth of the slope reduced the shear strength of loess and led to a failure.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Hong et al, (2021) based on their studies suggested that liquefaction could be the cause of some rapid landslides and great displacement in uniform loess slopes. Based on the eld survey and examination of a landslide that occurred in a village in the Xiangning Province of China in 2019, Shi et al, (2020) showed that the penetration of surface water into weak layers in the depth of the slope reduced the shear strength of loess and led to a failure.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the experiments are conducted under free‐surface or low‐normal‐stress conditions, in which the stress state is far from a real scale. Annular shear tests (Bagnold, 1954) and ring‐shear tests (Hong et al., 2021; Iverson et al., 1997) are also used to study the rheologies of solid‐fluid mixtures in a more controlled condition. Viscosity, which is the variation of shear resistance τ $\tau $ with shear strain rate trueγ˙ $\dot{\gamma }$, well describes the fluidity of granular flows (Hungr, 1995; Jeong et al., 2010; Wang et al., 2021).…”
Section: Introductionmentioning
confidence: 99%